Analysis of Rutin from Lespedeza virgata (Thunb.) DC. by Microwave-Assisted Extraction and Capillary Electrophoresis - Fan Zhang; Xiaohua Qi; Mingqiang Zou; Jinfeng Li (Journal of Chemistry)
A simple and rapid microwave-assisted extraction (MAE) technique was developed for the extraction of rutin from Lespedeza virgata (Thunb.) DC. The influence of four extraction variables on extraction of rutin was discussed. The optimum extraction conditions found were 75% aqueous ethanol, solvent volume to sample weight ratio at 90 : 1, extracting temperature at 75°C, and extraction time for 15 min. A comparison was made among MAE, classical maceration, and ultrasonic-assisted extraction (UAE). Yields were determined by high-performance capillary electrophoresis (HPCE). The whole analysis process was completed in ten minutes. The needful volumes of sample and buffer are very little. Compared with maceration and ultrasonic extraction, MAE is a rapid method with higher yield and less solvent consumption.